2013
DOI: 10.1073/pnas.1309907110
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of GDF-11 and myostatin activity by GASP-1 and GASP-2

Abstract: Myostatin (MSTN) and growth and differentiation factor-11 (GDF-11) are highly related TGF-β family members that have distinct biological functions. MSTN is expressed primarily in skeletal muscle and acts to limit muscle growth. GDF-11 is expressed more widely and plays multiple roles, including regulating axial skeletal patterning during development. Several MSTN and GDF-11 binding proteins have been identified, including GDF-associated serum protein-1 (GASP-1) and GASP-2, which are capable of inhibiting the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
103
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(119 citation statements)
references
References 40 publications
7
103
0
2
Order By: Relevance
“…Haidet et al (2008) found that in vivo viral delivery of a WFIKKN2 expression cassette into adult mice hind-limb and fore-limb muscle significantly increased overall body mass and the mass of the Tibialis anterior, Gastrocnemius, Quadriceps and Triceps muscles. Monestier et al (2012) observed that the over-expression of WFIKKN2 caused obvious increases in muscle mass resulting from hypertrophy rather than hyperplasia in a gain-of-function transgenic mouse model, and Lee and Lee (2013) further confirmed the effect of WFIKKN2 on muscle weight, describing how mice genetically engineered to lack WFIKKN2 had a shift in muscle fibre type from fast glycolytic typeIIb to fast oxidative typeIIa, as well as having impaired muscle regeneration ability. Taken together, this literature suggests that WFIKKN2 may be important in the regulation of muscle mass.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Haidet et al (2008) found that in vivo viral delivery of a WFIKKN2 expression cassette into adult mice hind-limb and fore-limb muscle significantly increased overall body mass and the mass of the Tibialis anterior, Gastrocnemius, Quadriceps and Triceps muscles. Monestier et al (2012) observed that the over-expression of WFIKKN2 caused obvious increases in muscle mass resulting from hypertrophy rather than hyperplasia in a gain-of-function transgenic mouse model, and Lee and Lee (2013) further confirmed the effect of WFIKKN2 on muscle weight, describing how mice genetically engineered to lack WFIKKN2 had a shift in muscle fibre type from fast glycolytic typeIIb to fast oxidative typeIIa, as well as having impaired muscle regeneration ability. Taken together, this literature suggests that WFIKKN2 may be important in the regulation of muscle mass.…”
Section: Introductionmentioning
confidence: 66%
“…In the developing human foetus, WFIKKN2 is expressed primarily in skeletal muscle (Trexler et al, 2002), and high levels of expression of WFIKKN2 have also been reported in the skeletal muscle of mice (Hill et al, 2003;Lee and Lee, 2013;Marcelo et al, 2009). Haidet et al (2008) found that in vivo viral delivery of a WFIKKN2 expression cassette into adult mice hind-limb and fore-limb muscle significantly increased overall body mass and the mass of the Tibialis anterior, Gastrocnemius, Quadriceps and Triceps muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Protein Expression and Purification-CHO cells stably overexpressing myostatin, GASP-1 and GASP-2 were used as previously published (4,19). Myostatin conditioned medium (CM) was concentrated ϳ10-fold using tangential flow and concomitantly buffer exchanged into 50 mM Tris pH 7.4, 500 mM NaCl and applied to a Lentil Lectin-Sepharose 4B (Amersham Biosciences) column.…”
Section: Methodsmentioning
confidence: 99%
“…GASP-1 and GASP-2-GASP-1 and GASP-2 was expressed and purified as published earlier with some minor modifications (19). Following application to butyl-Sepharose and heparin columns, the heparin eluent containing either GASP-1 or GASP-2 was dialyzed extensively into 50 mM Tris pH 7.4, 20 mM NaCl, 1 mM EDTA, applied to a MonoQ 10/100 GL column and eluted with a linear NaCl gradient.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation